A dual-stage low-power converter driving for piezoelectric actuator applied in flapping-wing micro aerial vehicles. (3rd June 2019) - Kong, Guoli; Su, Yu
It is essential for flapping-wing micro aerial vehicles to have a driver with compact size, low mass, and high conversion efficiency in low-power application. In this article, a dual-stage low-power converter driving for piezoelectric actuator was designed and implemented, which can be applied in flapping-wing micro aerial vehicles. Using the "simultaneous drive" method, an Residual Current Devices (RCD) passive snubber flyback DC/DC step-up converter cascaded with a bidirectional active half-bridge drive stage is designed. The flyback converter is controlled by pulse width modulation in discontinuous conduction mode to ensure the stability of the output high voltage. The half-bridge drive stage takes the approach of comparing the output voltage signal with an ideal waveform lookup table to generate arbitrary unipolar signals. The proposed converter has a weight of 345 mg, a size of 285 mm 2 (19 × 15 mm 2 ), a maximum output power of 500 mW, and a maximum conversion efficiency of 64.5%. An experiment driving for piezoelectric actuator was performed to observe the displacement generated by the converter. According to the experimental results, this converter can be applied in flapping-wing micro aerial vehicles.